Safety climate in 5 intensive care units:a nationwide hospital survey using the greek-cypriot version of the safety attitudes questionnaire - Pavlakis, Andreas; Raftopoulos, Vasilios (My University, 2013)
Background: Patient safety is considered an antecedent of quality of hospital care. The explicit need to focus on quality of care underpins the aim of the study to evaluate the safety culture and teamwork climate in the public intensive care units (ICUs) of the 5 regional public hospitals in Cyprus as measured by a validated safety attitudes tool. Methods: A questionnaire that included the Greek version of the generic version of the Safety Attitudes Questionnaire has been used in all public ICUs across Cyprus. Results: There were 132 (76.7%) fully completed questionnaires of 172 registered nurses who are currently positioned in Cyprus ICUs. The mean age of the participants was 33.09 ± 08.16 years. The mean of the total working years as a nurse was 10.82 ± 8.47 years, whereas the mean of the total work experience in the ICU units was 6.05 ± 5.16 years. The sample's age strongly correlated with teamwork, nurses with more years of experience rated higher teamwork (P = .02), and their perceptions of management were better than those of the inexperienced nurses. Conclusions: Considerable safety climate variations between the ICUs of the regional hospitals of Cyprus have been verified. Age, infrastructure, the severity of cases, and the nurse skill mix are variables that affect the patient safety culture in an ICU environment.
Keywords: Patient safety; Health surveys; Perception